2021
DOI: 10.7759/cureus.18770
|View full text |Cite
|
Sign up to set email alerts
|

Preferences Towards Electronically Exchanging Digital Images With Healthcare Providers Among US Adults

Abstract: Background: The rapid expansion of telemedicine, including teledermatology, during the COVID-19 pandemic has required both providers and patients alike to adapt to this digital transition. However, patient attitudes towards electronically shared images with their providers are poorly understood. To address this gap, we assessed digital image sharing preferences and associated determinants in a nationally representative sample.Methods: We analyzed pooled data from the Health Information National Trends Survey 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…Mean age of the study subjects was 34±22 years. Similar findings were report by Grace et al in US (Wei et al, 2021). This study showed that majority 16 (88.9%) of the patients who sought telemedicine consultation for gynaecology and obstetrics related were satisfied, similar study showed that 76% of telemedicine consults in obstetrics and gynaecology were successful.…”
Section: Discussionsupporting
confidence: 89%
“…Mean age of the study subjects was 34±22 years. Similar findings were report by Grace et al in US (Wei et al, 2021). This study showed that majority 16 (88.9%) of the patients who sought telemedicine consultation for gynaecology and obstetrics related were satisfied, similar study showed that 76% of telemedicine consults in obstetrics and gynaecology were successful.…”
Section: Discussionsupporting
confidence: 89%